Identifying coaching approaches that enable teachers' moral learning in professional learning communities. Issue 4 (27th July 2020) - Keijzer, Helma De; Jacobs, Gaby; Swet, Jacqueline Van; Veugelers, Wiel
Abstract : Purpose: This study sought to identify those approaches used by coaches that enable teachers' moral learning in professional learning communities (PLCs). Coaches who support moral learning focus on questioning values, beliefs and bias, which is in contrast with learning only (new) knowledge or skills. Design/methodology/approach: This was an exploratory case study. Eleven meetings of three PLCs were observed; each PLC consisted of four teachers and one teacher–coach. Semi-structured interviews with the coaches were conducted to gain information about their approaches. Data were analysed using supportive coaching approaches derived from educational literature. Findings: In total, 14 specific approaches regarding the support given by coaches for teachers' moral learning were identified. Four characteristics of coaches' attitudes that guided their approaches and seemed valuable in supporting moral learning were also identified. The findings showed the tensions the coaches encountered – for example, when balancing between offering a safe environment and encouraging critical reflection. Practical implications: With coaches' support, teachers can develop a more thoughtful understanding of the meaning of values, beliefs and bias for their actions in teaching practice. Social implications: Making explicit, and exploring precisely, what coaches do to support teachers' moral learning are useful for designing and improving professional development programmes that promote moral learning. Originality/value: The research reported in this paper outlines how coaches can encourage teachers' awareness of the impact of their actions on pupils, which, in turn, helps teachers to meet the complex moral challenges of their practice.